Sero-Prevalence of Hepatitis B and Hepatitis C Viruses among Tuberculosis Patients in Kassala, Eastern Sudan - Tajeldin M Abdallah; Mubarak I Idriss; Alzubair M Ahmed; Abdel-Aziem A Ali; Osman K Saeed (Global Journal of Infectious Diseases and Clinical Research - Peertechz Publications, 2015)
Background: Hepatitis B (HBV) and hepatitis C (HCV)virus infection is a major concern among tuberculous (TB) patients, thus early screening of these viruses will influence the outcome of the disease. Methods: A cross-sectional hospital based study, conducted at Kassala teaching hospital, Eastern Sudan, between June and December 2014 to investigate the sero-prevalence of HBV and HCV among TB patients. Sera samples were collected from patients and tested for HBSAg and anti-HCV bodies using immunochromtogrophic test (ICT) and enzyme-link immunosorbantassay (ELISA). Results: Out of 98 TB patients recruited in the study, HBSAg and anti HCV were detected in 15.3% and 1% patients using ELISA respectively, and in 17.3% and 3.1% patients by ICT respectively, one percent patient had both HBV and HCV co- infection. Conclusion: The sero-prevalence of HBV and HCV shown in this study call for urgent need to consider HBV and HCV screening in the national TB control program as this may reduce the risk of hepatotoxicity occurring during treatment of TB.